Organiser le soutien aux mobilisations de 2022-2023 en Iran. Lectures intersectionnelles et internationales - Lucia Direnberger; Sahar Aurore Saeidnia (Genre, Sexualité et Société)
This interview brings together the views and experiences of four feminist researchers and activists on the ongoing revolutionary mobilisations. Shirin and Gashin (pseudonyms) are Kurdish feminist researchers and activists in Paris. Nasrin Fathi (pseudonyms) and Fatemeh Masjedi are feminist researchers and activists in Berlin.